HIV/AIDS Among Young Women in Malawi: A Review of Risk Factors and Interventions - Nyalapa, McDonald W; Conn, Cath (School of Public Health and Psychosocial Studies, AUT University, 2019)
Young women aged 10-24 years in Malawi currently experience HIV prevalence of about 5%.  This high HIV prevalence amongst young women reflects a heart-breaking feature of the serious epidemic in southern Africa for the past five years. Given the serious situation it is vital to understand the risk factors faced by young women of Malawi, and further understanding of the interventions necessary to address the problem. A narrative review set out to explore the literature, retrieved from institutional reports and peer-reviewed publications, on the factors increasing young women’s vulnerability to HIV in Malawi, and on interventions aimed at reducing their risk. Young women in Malawi are particularly vulnerable to HIV infection as a result of poverty, harmful gender norms, and economic and social inequities. Whilst there are some interventions in place, in the face of such a disproportionately difficult social and socio-economic environment, lack of resources and other systemic gaps, these are not sufficiently effective. Given the scale of the problem and the difficult environment experienced by young women, effective HIV prevention interventions remain critical. Further research is required to establish appropriate and effective interventions, and to address the social determinants of health, especially in relation to gender and rights.
Keywords: HIV risk factors; HIV interventions; Girls; Young women; Malawi; Africa